Electronic Cigarette and Atherosclerosis: A Comprehensive Literature Review of Latest Evidences. (31st August 2022) - Damay, Vito Anggarino; Setiawan,; Lesmana, Ronny; Akbar, M. Rizki; Lukito, Antonia Anna; Tarawan, Vita M.; Martha, Januar W.; Nugroho, J.
Abstract : Coronary artery diseases (CAD), also known as coronary heart disease (CHD), are the world's leading cause of death. The basis of coronary artery disease is the narrowing of the heart coronary artery lumen due to atherosclerosis. The use of electronic cigarettes has increased significantly over the years. However, harmful effects of electronic cigarettes are still not firm. The aim of this article is to review the impact of electronic cigarette and its role in the pathogenesis of atherosclerosis from recent studies. The results showed that several chemical compounds, such as nicotine, propylene glycol, particulate matters, heavy metals, and flavorings, in electronic cigarette induce atherosclerosis with each molecular mechanism that lead to atherosclerosis progression by formation of ROS, endothelial dysfunction, and inflammation. Further research is still needed to determine the exact mechanism and provide more clinical evidence.